Jack Reacher : The Sentinel - Book 25 - Child, Lee; Child, Andrew 1968-; Brick, Scott; Rooney, Christina; Random House Audio Publishing (New York, New York : Random House Audio, an imprint of the Penguin Random House Audio Publishing Group,|c℗2020., 2020)
As always, Reacher has no particular place to go, and all the time in the world to get there. One morning he ends up in a town near Pleasantville, Tennessee. But there's nothing pleasant about the place. In broad daylight, Reacher spots a hapless soul walking into an ambush. 'It was four against one,' so Reacher intervenes, with his own trademark brand of conflict resolution. The man he saves is Rusty Rutherford, an unassuming IT manager, recently fired after a cyberattack locked up the town's data, records, information and secrets. Rutherford wants to stay put, look innocent, and clear his name. Reacher is intrigued. There's more to the story. The bad guys who jumped Rutherford are part of something serious and deadly, involving a conspiracy, a cover-up, and murder, all centered on a mousy little guy in a coffee-stained shirt who has no idea what he's up against. Rule one: if you don't know the trouble you're in, keep Reacher by your side.
Keywords: Reacher, Jack -- (Fictitious character) -- Fiction; Reacher, Jack -- (Fictitious character); Ex-police officers -- Fiction; Cyberterrorism -- Fiction; Conspiracies -- Fiction; Computer security -- Fiction; Murder -- Fiction -- Investigation; Nashville (Tenn.) -- Fiction; Thrillers (Fiction); Audiobooks